Basal and Adrenocorticotropic Hormone Stimulated Plasma Cortisol Levels Among Egyptian Autistic Children: Relation to Disease Severity - Hewedi Doaa H; Hamza Rasha T; Ismail Mona A (BMC, 2010)
Abstract Background Autism is a disorder of early childhood characterized by social impairment, communication abnormalities and stereotyped behaviors. The hypothalamic-pituitary-adrenocortical (HPA) axis deserves special attention, since it is the basis for emotions and social interactions that are affected in autism. Aim To assess basal and stimulated plasma cortisol, and adrenocorticotropic hormone (ACTH) levels in autistic children and their relationship to disease characteristics. Methods Fifty autistic children were studied in comparison to 50 healthy age-, sex- and pubertal stage- matched children. All subjects were subjected to clinical evaluation and measurement of plasma cortisol (basal and stimulated) and ACTH. In addition, electroencephalography (EEG) and intelligence quotient (IQ) assessment were done for all autistic children. Results Sixteen% of autistic patients had high ACTH, 10% had low basal cortisol and 10% did not show adequate cortisol response to ACTH stimulation. Autistic patients had lower basal (p = 0.032) and stimulated cortisol (p = 0.04) and higher ACTH (p = 0.01) than controls. Childhood Autism Rating Scale (CARS) score correlated positively with ACTH (r = 0.71, p = 0.02) and negatively with each of basal (r = -0.64, p = 0.04) and stimulated cortisol (r = -0.88, p < 0.001). Hormonal profile did not differ in relation to EEG abnormalities, IQ and self- aggressive symptoms. Conclusions The observed hormonal changes may be due to a dysfunction in the HPA axis in autistic individuals. Further studies are warranted regarding the role of HPA axis dysfunction in the pathogenesis of autism.